2021
DOI: 10.1002/advs.202003721
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Fatty Acid Binding Protein Promotes the Onset and Progression of Liver Fibrosis via Mediating the Crosstalk between Liver Sinusoidal Endothelial Cells and Hepatic Stellate Cells

Abstract: Development of liver fibrosis results in drastic changes in the liver microenvironment, which in turn accelerates disease progression. Although the pathological function of various hepatic cells in fibrogenesis is identified, the crosstalk between them remains obscure. The present study demonstrates that hepatic expression of adipocyte fatty acid binding protein (A‐FABP) is induced especially in the liver sinusoidal endothelial cells (LSECs) in mice after bile duct ligation (BDL). Genetic ablation and pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Further investigation of the literature shows that protein expression of these signature genes are indeed associated with a damaged LSEC phenotype in mice and human. For example, FAPB4 , also known as (adipocyte) fatty acid binding protein 4, was recently found to be upregulated in LSECs during liver fibrosis, can promote LSEC capillarization and is suggested to be a key regulator involved in the onset and progression of fibrosis in two liver fibrosis models in mice ( 58 ). In addition, FABP4 is also overexpressed in patients with HCC ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation of the literature shows that protein expression of these signature genes are indeed associated with a damaged LSEC phenotype in mice and human. For example, FAPB4 , also known as (adipocyte) fatty acid binding protein 4, was recently found to be upregulated in LSECs during liver fibrosis, can promote LSEC capillarization and is suggested to be a key regulator involved in the onset and progression of fibrosis in two liver fibrosis models in mice ( 58 ). In addition, FABP4 is also overexpressed in patients with HCC ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vWf + LSECs were significantly correlated to the fibrosis stage in patients with cirrhosis ( 63 ) and a higher vWF expression has been linked to old age and pseudocapilarization ( 64 ). Targeting LSECs to alleviate fibrosis through one of these 4 genes could be an option as it was recently shown that the treatment with the FABP4 selective inhibitor BMS309403 alleviated lipopolysaccharide induce acute liver injury and high fat diet-induced NASH in mice ( 65 ), and a knockout of FABP4 reduces fibrosis in CCl 4 and bile duct ligation model in mice ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study further showed that AFABP expression was increased in liver sinusoidal endothelial cells in mice with liver fibrosis. AFABP enhanced liver sinusoidal endothelial cell capillarization and potentiated liver fibrosis through augmenting transforming growth factor beta‐1 production in the hepatic stellate cells 58 . Importantly, preclinical studies had shown that pharmacological inhibition of AFABP could alleviate both NASH and liver fibrosis in mice, highlighting AFABP as a potential therapeutic target in NAFLD and type 2 diabetes 51,58 .…”
Section: Dysfunctional Adipose Tissue As a Common Soil For Nafld In T...mentioning
confidence: 99%
“…For instance, quiescent HSCs store retinoid droplets (vitamin A) and express glial fibrillary acidic protein (GFAP), whereas activated cells do not (Yanguas et al., 2016). Upon activation, HSCs not only become the main source of the fibrous components in the injured liver (Lee & Friedman, 2020), but also perpetuate the fibroinflammatory processes by autocrine or paracrine communication (Li et al., 2008) with hepatocytes (Chung et al., 2016; Dong et al., 2021), Kupffer cells (Cai et al., 2018; Corbett et al., 2015), and liver sinusoidal endothelial cells (Piao et al., 2019; Wu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%